Historia de la comunicación de Ecuador “Democracia Inestable: partidos políticos y prensa en el fin de siglo (1979-2000)” y la “Crisis Bancaria y los cambios en el panorama mediático” (2000-2012). - Pesantes Peña, Karla Andrea (2014)
This current thesis takes as bibliographic references Ecuadorian newspapers and magazines issued from the return to democracy in 1979 till 2000, also considers visual and radio contents. Both printed materials are being used to evaluate Ecuador’s Communications History. In order to analyze the political tension it was necessary to recall political facts in Ecuador like “Sucretizacion” or the conversion of private debts from dollars to local currency (sucres), corruption cases during Sixto Duran Ballen’s government and the Civil Revolution known as “The Forajidos”. In all this facts described the private media in Ecuador, particularly the radio, had a preponderant participation. Also this work makes a recount of the abuses and persecutions to journalists described as a freedom of press assaults during the regimes of Leon Febres Cordero, Abdala Bucaram, Lucio Gutierrez and Rafael Correa. These governments constitute the most recent history of democracy in Ecuador. Finally the thesis addresses the Financial Crisis of 1999, a time which part of the private media was in the bankers’ hands. It’s been examined the changes on the media panorama during and after this economical crisis. Throughout these pages it’s possible to evidence that after the 1999’s crisis Ecuador adopted new laws regarding the banks’ ownership and also how the Ecuadorian government has become the biggest media conglomerate in the country.